2021
DOI: 10.3390/jof7060481
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmosis Diagnosed in Europe and Israel: A Case Report and Systematic Review of the Literature from 2005 to 2020

Abstract: Human histoplasmosis is a mycosis caused by two distinct varieties of a dimorphic fungus: Histoplasma capsulatum var. capsulatum and H. capsulatum var. duboisii. In Europe, it is usually imported by migrants and travellers, although there have been some autochthonous cases, especially in Italy; however, most European physicians are unfamiliar with its clinical and pathological picture, particularly among immunocompromised patients without HIV infection. This systematic review of all the cases of histoplasmosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 146 publications
2
16
1
2
Order By: Relevance
“…Although the occurrence of Hcd infection is largely attributed to Africa, several cases have been reported outside Africa including indigenous case reports [69,74,75]. This is corroborated in an earlier review by Antinori et al and Develoux et al which also confirmed significant number of Hcd infection cases reported outside Africa [74,75]. Our review demonstrates the occurrence of Hcd infection as a worldwide disease entity contrary to the previous opinion that all cases are contracted from Africa.…”
Section: Discussionsupporting
confidence: 90%
“…Although the occurrence of Hcd infection is largely attributed to Africa, several cases have been reported outside Africa including indigenous case reports [69,74,75]. This is corroborated in an earlier review by Antinori et al and Develoux et al which also confirmed significant number of Hcd infection cases reported outside Africa [74,75]. Our review demonstrates the occurrence of Hcd infection as a worldwide disease entity contrary to the previous opinion that all cases are contracted from Africa.…”
Section: Discussionsupporting
confidence: 90%
“…Out of 25 meta-analyses/systematic reviews on histoplasmosis, four met inclusion criteria and showed a male predominance ranging from 68% to 100%. [101][102][103][104] Details on selection process as well as results can be found in the online supplement.…”
Section: Histoplasmosismentioning
confidence: 99%
“…В недавней работе Antinori с соавторами было отмечено, что при обследовании лиц с иммунодефицитными состояниями культуральный метод использовали в 46,4-57,5% случаев, гистологические исследования -в 58,4-78,6%. При обследовании иммунокомпетентных лиц на долю диагностических мероприятий, связанных с культуральным или гистологическим методами приходилось 12,3% случаев, а наибольшее внимание уделялось иммунологическим тестам -44,4% [5].…”
Section: культуральные и гистологические исследованияunclassified
“…Не исключено, что из-за фенотипических различий штаммов Histoplasma spp. могут варьировать аналитические характери-чего возрастает вероятность регистрации завозных случаев гистоплазмоза на неэндемичные территории [3,4,5]. Во внешней среде H. capsulatum обитает в загрязненной пометом птиц и/или летучих мышей почве в мицелиальной форме.…”
Section: Introductionunclassified